The Role of Tumor Deposits in Predicting the Efficacy of Chemotherapy in Stage III Colon Cancer - Shi, Mingyu; Zhang, Hongzhi; Yao, Guozhong; Wu, Jianjun; Zhu, Chuming; Zhang, Xu; Ren, Yuan (Frontiers in Oncology, 2020)
Purpose: To evaluate the role of tumor deposits in predicting the efficacy of chemotherapy in stage III colon cancer. Methods: Using the SEER*Stat software Version 8.3.6, we recruited colon cancer patients diagnosed between 2004 and 2016 from a national cohort. We used the x2 (Chi-square) test to compare differences between different categorical variables according to the number of tumor deposits. The Cox proportional hazards regression model was used to determine the independent association of different clinical and pathological variables with CSS, which were adjusted for other common prognostic factors. Results: We have identified 29017 patients diagnosed with stage III colon cancer from the Surveillance, Epidemiology and End Results (SEER) database. The results of multivariate analyses showed that patients with the receipt of chemotherapy had 54.7% decreased risk of cancer-specific mortality compared with those not (HR = 0.453, 95%CI = 0.425-0.483, P < 0.0001) in no Tumor deposits (TDs) group; In 1-2 TDs group, patients with the receipt of chemotherapy had 56.8% decreased risk of cancer-specific mortality compared with those not (HR = 0.432, 95%CI = 0.364-0.512, P < 0.0001); In ≥3 TDs group, patients with the receipt of chemotherapy had 51.8% decreased risk of cancer-specific mortality compared with those not (HR = 0.482, 95%CI = 0.389-0.597, P < 0.0001). Conclusions: Our study demonstrated that the presence of TDs was associated with a dismal prognosis and high number of TDs would also contribute to the worse survival of colon cancer. High number of TDs did not affect the survival benefit of chemotherapy in stage III colon cancer.